The Impact of Rising of Fuel Prices on Sectoral Output in Indonesia - Afiska Primadewi; Firmansyah Firmansyah (Journal of Economics and Business, 2024)
In 2022, the Indonesian government reallocated fuel subsidies, resulting in an average increase in fuel prices by 30%. This research aims to determine the impact of the fuel price increase on sectoral output and total output in Indonesia. The study utilizes time series data from 1980 to 2022, which is then analyzed using regression analysis with the Partial Adjustment Model (PAM) and Input-Output analysis with the classification of 185 sectors. By simulating a 30% increase in fuel prices, this study found that the fuel price hike would decrease sectoral output and total output. Additionally, the research identified the transportation sector as the most affected sector..